Biotransformation of ibuprofen in biological sludge systems: Investigation of performance and mechanisms. (1st March 2020) - Jia, Yanyan; Yin, Linwan; Khanal, Samir Kumar; Zhang, Huiqun; Oberoi, Akashdeep Singh; Lu, Hui
Abstract: Ibuprofen (IBU), a common non-steroidal anti-inflammatory drug (NSAID), is widely used by humans for controlling fever and pain, and is frequently detected in the influent of wastewater treatment plants and different aquatic environments. In this study, the biotransformation of IBU in activated sludge (AS), anaerobic methanogenic sludge (AnMS) and sulfate-reducing bacteria (SRB)-enriched sludge systems was investigated at three different concentrations of 100, 500 and 1000 μg/L via a series of batch and continuous studies. IBU at concentration of 100 μg/L was effectively biodegraded by AS whereas AnMS and SRB-enriched sludge were less effective in IBU biodegradation at all concentrations tested. However, at higher IBU concentrations of 500 and 1000 μg/L, AS showed poor IBU biodegradation and chemical oxygen demand (COD) removal due to inhibition of aerobic heterotrophic bacteria (i.e., Candidatus Competibacter) by IBU and/or IBU biotransformation products. The microbial analyses showed that IBU addition shifted the microbial community structure in AS, AnMS and SRB-enriched sludge systems, however, the removals of COD, nitrogen and sulfur in both anaerobic sludge systems were not affected significantly ( p > 0.05). The findings of this study provided a new insight into biotransformation of IBU in three important biological sludge systems. Graphical abstract: Image 1 Highlights: Removal of Ibuprofen (IBU) in three biological sludge systems was comparatively investigated. AnMS and SRB-enriched sludge systems were less effective in IBU biodegradation. IBU was effectively biotransformed in AS system at lower IBU concentration of 100 μg/L. Aerobes were significantly inhibited at high IBU concentrations (500 and 1000 μg/L) in AS system.